1965
DOI: 10.1021/jf60139a021
|View full text |Cite
|
Sign up to set email alerts
|

Bean Lipids, Lipid Composition of Dry Beans and Its Correlation with Cooking Time

Abstract: The triglyceride and phosphatide contents of seven varieties or types of dry beans and the Alaska pea were determined. The triglyceride content ranged from 0.89% for Alaska peas to 1.54% for Michelite beans. The phosphatide content averaged near 1 %, except for lima beans which averaged 0.88%. Gas-liquid chromatography was used to study the component fatty acids of the triglycerides and phosphatides. The main fatty acids of the triglycerides were palmitic, oleic, linoleic, and linolenic. Small amounts of myris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1973
1973
1990
1990

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…This increase in cooking time causes increased loss of some nutritional qualities and increases usage of scarce fuel resources. out any changes in fat (Takayama et al 1965), or pectin (Kon 1968) as a cause for this increase in cooking time. Previous results in our laboratory (Kon 1979) indicated that changes in organic phosphate content might have an effect on the cooking time for beans.…”
Section: Introductionmentioning
confidence: 93%
“…This increase in cooking time causes increased loss of some nutritional qualities and increases usage of scarce fuel resources. out any changes in fat (Takayama et al 1965), or pectin (Kon 1968) as a cause for this increase in cooking time. Previous results in our laboratory (Kon 1979) indicated that changes in organic phosphate content might have an effect on the cooking time for beans.…”
Section: Introductionmentioning
confidence: 93%
“…Takayama et al 163 studied the lipid composition of several legumes including several types of dry beans and Alaska peas in an unsuccessful attempt to find a correlation with cooking time. Hydar and Hadziyev 67 studied pea lipid oxidation on protein and carbohydrate matrices and concluded that lipid polarity, rather than unsaturation, Volume 17, Issue 2 127 controlled lipid oxidation.…”
Section: B Changes In Lipids During Processingmentioning
confidence: 99%
“…This was attributed, in part, to a high content of polyunsaturated fatty acids such as linoleic and linolenic acids in legumes. 11 *' 43 ' 99 ' 151 ' 163 Studies with rabbits by Krischevsky et al 86 indicate that peanut oil is atherogenic. Isaacks et al 70 reported that diets of up to 30% soybean oil resulted in increased growth and feed efficiency in the chick.…”
Section: A Nutritional Aspects Of Legume Lipidsmentioning
confidence: 99%
“…Lipid content and unsaturated fatty acid composition of peas and various mature beans are summarized in Table I. Since the values for unsaturated fatty composition can vary (15,(19)(20)(21) depending on crop year, state of maturity and variety, the reported amounts will be used solely to develop our theme on their potential to oxidize. The lipid content for all the legumes except soybeans listed in Table I triglyceride with only about 2.5-2.8% phospholipid, based on phosphorous analysis, while the other legumes contain equal amounts of these two.…”
Section: Pea and Bean Lipidsmentioning
confidence: 99%